Beyond perestroika : axiology and the new Russian entrepreneurs - Gallopin, Gary G. (Value Inquiry Book Series, 2009)
This book investigates rapid societal change in Russia during the early 1990s. The story of the anthropologist (author) and the people he studied reveals cultural similarities and differences between them. Russians and Latvians taught the author about the Soviet Union, its people, and its cultures. Formal axiology provides a novel way to access their changing values.